EFFECT OF ASIATIC MANGROVE (RHIZOPHORA MICRONATA) LEAVES EXTRACT AS ANALGESIC IN MALE ALBINO DDW MICE (MUS MUSCULUS L.) INDUCED BY 0,7% ACETIC ACID - Nanuru, Erika Widianingsih; Dewi, Lestari; Wibowo, Prajogo (UNUSA Press, 2021)
Background : Pain is an unpleasant emotional experience that illustrates ongoing tissue damage. Excessive use of non-steroidal anti-inflammatory drugs can cause peptic ulcer to gastric mucosal damage and perforation. Indonesia contains the largest area of mangrove forest in the world. There are 45 species of mangrove found and one of them is Asiatic Mangrove (Rhizophora mucronata). This type is easy to find and rich of alkaloids and flavonoids which can be used as analgesics. Method: This study used post-test only control group design. The number of mice that used was 25 mice, divided into 5 groups. Which were given different therapies aquadest 10mL/KgBW, acetosal 150 mg/KgBW, extract of Rhizophora mucronata 250 mg/KgBW, 500 mg/KgBW, and 1000 mg/kg bw. The pain was induced by 0,7% glacial acetic acid at a dose of 10 mL/KgBW. The writhes of the mice was being calculated with an interval of 10 minutes in 30 minutes. Result: The results of the analysis showed the decrease in writhes of mice in acetosal group dose 150 mg/kg bw, Rhizophora mucronata leaves extract dose 250 mg/kg bw, 500 mg/kg bw, and 1000 mg/kg bw. There was a significant difference in the results of the Mann-Whitney U test with p<0,05 in the aquadest group and the acetosal group with the Rhizophora mucronata leaves extract group dose 500 mg/kg bw, the difference between the acetosal group and the Rhizophora mucronata leaves extract group dose 250 mg/kg bw, and the difference between the Rhizophora mucronata leaves extract group dose 500 mg/kg bw and the Rhizophora mucronata leaves extract group dose 1000 mg/kg bw. Conclusion: Rhizophora mucronata leaves extract dose 500 mg/kg bw can provide analgesic effect and can reduce the writhing frequency in mice much better than acetosal group.